Five years follow up of patient receiving prolonged mechanical ventilation: Data for a single center in Taiwan - Huang, Chienhsiu (Frontiers in Medicine, 2022)
Background: The National Association for Medical Direction of Respiratory Care recommended tracking 1-year survival rates (the most relevant outcome) in patients treated with prolonged mechanical ventilation. However, patients treated with prolonged mechanical ventilation had higher mortality rates within the first 2 years after weaning. More knowledge regarding long-term mortality would help patients, families, and clinicians choose appropriate interventions and make end-of-life decisions. In this study, we sought to explore the long-term mortality rates for all patients treated with prolonged mechanical ventilation over a period of ten years. Objective: The present study aimed to improve the overall survival outcomes of patients treated with prolonged mechanical ventilation by identifying the factors affecting the 5-year mortality rates for these patients. Design: retrospective observational study Methods: In this retrospective study, we explored the influential factors related to the overall survival outcomes of all patients treated with prolonged mechanical ventilation. We enrolled all those who were consecutively admitted to the weaning unit between 1 January 2012 and 31 December 2016. Each patient's length of survival was calculated from admission to the weaning unit until death or December 31, 2021. We analyzed the data to investigate the survival time, mortality rates, and survival curves in these patients. Results: We gathered long-term follow-up data on 296 patients treated with prolonged mechanical ventilation. There were better mean survival times in patients treated with prolonged mechanical ventilation with the following characteristics (in order): no comorbidities, tracheostomies, and intracranial hemorrhage. Successful weaning, receipt of tracheostomy, an age less than 75 years, and no comorbidities were associated with better long-term overall survival outcomes. Conclusions: Prolonged mechanical ventilation patients had abysmal overall survival outcomes. Despite the tragedy of long-term survival outcomes of prolonged mechanical ventilation patients, clinicians should never give up on the dream of improving long-term outcomes.